Supply chain management maturity assessment: challenges of the enterprises in Serbia - Radosavljevic, Marija; Barac, Nada; Jankovic-Milic, Vesna; Andjelkovic, Aleksandra (Journal of Business Economics and Management, 2016)
Nowadays competition has been spread to supply chains, instead of individual enterprises. Therefore, beside evaluation of enterprise’s capabilities to manage business processes, it is important to assess capabilities for business process management at supply chain level. The purpose of the research presented in this paper is to point out the necessity of supply chain management maturity in implementation of best practice. Research methodology is based on supply chain management maturity models. Application of the Delphi method enabled usage of maturity model, adapted to the enterprises in Serbia. The value of the research precedes from unique combination of best practice elements for the assessment of supply chain management maturity level. The research results show that best practice elements are not very popular in the enterprises in Serbia. All enterprises are at the second and third maturity level. Bearing in mind that everything has to be improved continually, maturity models, proposed by different authors can be further developed by including certain statistical tools. The original contribution of this paper and its practical implication refer to including statistical tools, hierarchical cluster analysis and correlation, into maturity analysis, thus enabling creation of framework as a road-map for the improvement of supply chain management maturity.